Fabrication and characterization of millimeter-scale translucent La2O3-doped Al2O3 ceramic hollow spheres. (April 2016) - Li, Haoting; Liao, Qilong; Dai, Yunya; Wang, Fu; Wang, Haiyang; Li, Xibo
Graphical abstract: Highlights: Millimeter-scale translucent La2 O3 -doped Al2 O3 hollow spheres have been prepared. The diameters of the prepared hollow spheres are 500–1300μm. The degree of sphericity for the prepared hollow spheres is above 98%. The mechanisms of transparency are discussed. Abstract: Millimeter-scale translucent La2 O3 -doped Al2 O3 ceramic hollow spheres have been successfully prepared using the oil-in-water (paraffin-in-alumina sol) droplets as precursors made by self-made T-shape micro-emulsion device. The main crystalline phase of the obtained hollow sphere is alpha alumina. The prepared translucent La2 O3 -containing Al2 O3 ceramic hollow spheres have diameters of 500–1300 μm, wall thickness of about 23 μm and the degree of sphericity of above 98%. With the increase of the La2 O3 content, grains and grain-boundaries of the alumina spherical shell for the prepared millimeter-scale hollow spheres become regular and clear gradually. When the La2 O3 content is 0.1 wt.%, the crystal surface of the obtained Al2 O3 spherical shell shows optimal grains and few pores, and its transmittance reaches 42% at 532 nm laser light. This method provides a promising technique of preparing millimeter-scale translucent ceramic hollow spheres for laser inertial confined fusion.